Kemampuan Berpikir Kritis Mahasiswa Pendidikan Biologi Melalui Penyelesaian Masalah Lingkungan - Santi, Nuzulia; Soendjoto, Mochamad Arief; Winarti, Atiek (Department of Biology Education Faculty of Teacher Training and Education Sebelas Maret Un, 2018)
Critical thinking ability is important to be possessed by every individual, especially in the era of globalization. The ability to think critically supports the individual to overcome the problems in life, among which environmental problems are. Individuals and environments cannot be separated, the relationship between them is reciprocal. Solutions to environmental problems can be realized through critical thinking. Each individual's critical thinking ability varies, depending on the frequency of frequent exercises to develop that ability. Such exercises include frequently asking questions, posing assumptions, identifying information, making inferences, identifying impacts, and so on. It is therefore important to identify the critical thinking skills of individuals in a forum. Description of the ability to think critically about environmental problems is expected to be the basis for the design of development of learning plan set related to the subject of Environmental Knowledge. The description of students' critical thinking ability is obtained through questions prepared according to Polya’s problem solving syntax. The set of questions contains elements of reasoning that are judged based on the intellectual standards of reasoning by Paul and Elder.